2004
DOI: 10.1073/pnas.0406614101
|View full text |Cite
|
Sign up to set email alerts
|

Combining biological networks to predict genetic interactions

Abstract: Genetic interactions define overlapping functions and compensatory pathways. In particular, synthetic sick or lethal (SSL) genetic interactions are important for understanding how an organism tolerates random mutation, i.e., genetic robustness. Comprehensive identification of SSL relationships remains far from complete in any organism, because mapping these networks is highly labor intensive. The ability to predict SSL interactions, however, could efficiently guide further SSL discovery. Toward this end, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
226
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(236 citation statements)
references
References 47 publications
(41 reference statements)
10
226
0
Order By: Relevance
“…Our method extends beyond previous work that has used physical interaction networks to predict genetic interactions (Wong et al 2004;Kelley and Ideker 2005;Le Meur and Gentleman 2008) and we demonstrated that considering functional interactions offers improved predictive power. Two reasons for this are the integration of many more diverse datasets and the fact that functional couplings transcend physical interactions.…”
Section: Discussion Functional Network Provide a General Strategy Fomentioning
confidence: 52%
See 3 more Smart Citations
“…Our method extends beyond previous work that has used physical interaction networks to predict genetic interactions (Wong et al 2004;Kelley and Ideker 2005;Le Meur and Gentleman 2008) and we demonstrated that considering functional interactions offers improved predictive power. Two reasons for this are the integration of many more diverse datasets and the fact that functional couplings transcend physical interactions.…”
Section: Discussion Functional Network Provide a General Strategy Fomentioning
confidence: 52%
“…Previous work has shown that it is possible to predict genetic interactions using physical protein-protein interaction networks Wong et al 2004;Kelley and Ideker 2005;Le Meur and Gentleman 2008). We therefore asked whether using functional interactionswhich extend beyond physical interactions-improves the predictive power of a network.…”
Section: Functional Network Are More Predictive Than Current Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Orthogonal sets of data (i.e., protein interactions, protein localization, gene expression arrays), from different cellular conditions are proving useful for network analysis [49,50]. To provide deeper functional insight into protein interaction networks, the relevant modules (domains and linear motifs) within a network can be used to decipher its observed interactions (i.e., domain-domain or motif-domain), and to predict their stability.…”
Section: Topologies and Architectures Of Modular Interaction Networkmentioning
confidence: 99%